The protein kinase R modifies gut physiology to limit colitis - Yim, Howard Chi Ho; Chakrabarti, Arindam; Kessler, Sean; Morimoto, Hiroyuki; Wang, Die; Sooraj, Dhanya; Ahmed, Afsar U.; de la Motte, Carol; Silverman, Robert H.; Williams, Bryan RG.; Sadler, Anthony J. (Frontiers in Immunology, 2023)
Here we investigate the function of the innate immune molecule protein kinase R (PKR) in intestinal inflammation. To model a colitogenic role of PKR, we determine the physiological response to dextran sulfate sodium (DSS) of wild-type and two transgenic mice strains mutated to express either a kinase-dead PKR or to ablate expression of the kinase. These experiments recognize kinase-dependent and -independent protection from DSS-induced weight loss and inflammation, against a kinase-dependent increase in the susceptibility to DSS-induced injury. We propose these effects arise through PKR-dependent alteration of gut physiology, evidenced as altered goblet cell function and changes to the gut microbiota at homeostasis that suppresses inflammasome activity by controlling autophagy. These findings establish that PKR functions as both a protein kinase and a signaling molecule in instituting immune homeostasis in the gut.